Principle of privacy in Islamic architectural design context: a systematic literature review - Dini, Ariani Mohammad; Salih, Sarah Abdulkareem; Ismail, Sumarni; Asif, Nayeem; Sabil, Azmal (Human Resource Management Academic Research Society, 2023)
Privacy has a significant role in formulating the elements of traditional Islamic architecture due to its critical importance in Islamic law. However, the birth of modern and contemporary architecture brought by modern trends and rapid urbanization created a diminishing sense of privacy and comfort to the building users. Besides, there is a lack of understanding and body of knowledge about privacy from an architectural perspective. Therefore, the present study aims to investigate the traditional design elements that promote privacy and provide a conceptual definition of privacy from an Islamic architectural perspective. The methodology used is a systematic literature review of English language literature published in two electronic databases (Scopus and ScienceDirect), using MeSH terms, keywords, and inclusion and exclusion criteria. The results of this study confirm that the principle of privacy plays a critical role in architectural design consideration, especially in residential areas. The conceptual definitions classify privacy as either a sociophysical aspect (physical, social, and psychological) or a sensory aspect (visual, acoustic and olfactory). Importantly, the key design elements for promoting privacy are the central courtyard, exterior facade, Mashrabiya, floor plans and spatial arrangement, subtle design approaches, transitional design elements, and neighbourhood urban configuration. The findings contribute to a guideline for urban planners and architects to understand better the privacy concept and its design elements to enhance the functional architecture in an Islamic context that respects the user's privacy and comfort.